Atividade inseticida de palicourea marcgravii st. Hil. (rubiaceae) e piper aduncum l. (piperaceae) sobre cigarrinha (aetalion sp.), praga de importância econômica no Amazonas - Silva, Wilson Castro (2005)
The use of extracts of toxic and medicinal plants, usually under exploited in Amazonia, is an alternative to control phytophagous insects due to their low costs, easy preparation, use and environmental safety. The lack of papers about the insecticidal activity of Palicourea marcgravii and Piper aduncum on treehopper (Aetalion sp.) was the reason to carry out this research. The aim of this work was to evaluate the insecticidal action of P. marcgravii and P. aduncum on Aetalion sp. Adult insects were collected on the tree Clitoria fairchildiana, separated in groups of ten individuals into plastic vessels and exposed to topic application of aqueous extracts of leaves and roots of both plant species. The extracts of leaves and roots of P. marcgravii were applied at the concentrations of 30, 40 and 50 mg/mL and 10, 20 and 30 mg/mL, respectively, whereas for P. aduncum the extracts were applied at the concentrations of 10, 20 and 30 mg/mL, for both extracts of leaves and roots. The control groups were treated with distilled water. After the treatments, the vessels were transferred to a greenhouse and maintained under natural conditions of temperature, light and humidity. The tests lasted 48 h and every 12 h the mortality rate was evaluated. The experiments were performed in a complete randomized design with three treatments in five replicates more a attest group. The data were evaluated using One-way Analysis of Variance (ANOVA) followed by a multiple comparison method (Dunnett’s test). The Probit method was used for calculation of the median lethal concentration (LC50) and the median lethal time (LT50) values, and their 95% confidence limits. The computer program TOXRAT® was used for the Probit analysis and to fit the dose-response curves. The extract of roots of P. marcgravii was the most toxic (LC50 = 12,4 mg/mL), but not statistically different from the P. aduncum extracts (leaves and roots, LC50 = 20,9 and 20,9 mg/mL, respectively). The extracts of P. aduncum were toxic in shorter exposure time (leaves and roots, LT50 = 30,2 and 22,3 h, respectively) than the P. marcgravii extracts (leaves and roots, LT50 = 41,2 and 34,9 h, respectively), but not statistically different. The extracts of both species showed insecticidal action on Aetalion sp., however, more detailed studies about the chemical composition of the extracts and their toxicity for non-target (beneficial) organisms should be done before to recommend them as insecticides.